Thermal enhancement in microfluid passages by synthetic jets - Chandratilleke, Tilak; Jagannatha, Deepak; Narayanaswamy, Ramesh (Research Publishing Services, 2010)
This paper examines the characteristics of a pulsating fluid jet known as synthetic jet and its cooling effectiveness for heated micro fluid passages. The jet mechanism uses an oscillating diaphragm to inject a high-frequency fluid jet with a zero net mass flow through the jet orifice. The pulsed jet and the micro passage flow interaction is modelled as a 2-dimensional finite volume simulation with unsteady Reynolds averaged Navier-Stokes equations. For a range of conditions, the special characteristics of this periodically interrupted flow are identified while predicting the associated convective heat transfer rates. The results indicate that the pulsating jet leads to outstanding thermal performance in the micro passage increasing its heat dissipation by about 4.3 times compared to a micro passage without jet interaction within the tested parametric range. The degree of enhancement is first seen to grow gently and then rather rapidly beyond a certain flow condition to reach a steady value. The proposed strategy has the unique intrinsic ability to generate outstanding degree of thermal enhancement in a micro passage without increasing its flow pressure drop. The technique is envisaged to have application potential in miniature electronic devices where localised cooling is desired over a base heat dissipation load.